The Impact of Covid-19 Pandemic on Land Surface Temperature in Yogyakarta Urban Agglomeration - Erlyna Nour Arrofiqoh; Devika Ayu Setyaningrum (Journal of Applied Geospatial Information, 2021)
Since the end of 2019, the world has been surprised by Corona Virus (COVID-19) pandemic. The first case of COVID-19 in Indonesia was reported in March 2020. The Indonesian policymakers have announced to limit social interaction by applying physical distancing and appealed to stay at home to slow the spread of COVID-19. Yogyakarta city is known as a tourism city and student city also affected by the presence of COVID-19. Many tourist destinations, schools, colleges, institutions, companies, and industries not operating as usually because people have been appealed to work and study at home. Less outdoor activities caused the vehicle emission in the street is rarely. This condition makes the temperature is cooler. This paper aimed to analyze the impact of the COVID-19 pandemic on the land surface temperature. Landsat 8 satellite data has been used to show the changes in LST before the pandemic, during a pandemic, and after the new normal. The results showed that during the emergence of the COVID-19 pandemic with reducing outdoor activities, the LST was lower than before the pandemic. Whereas after the new normal, the LST was increased.